Follow-Up of a Rare Case of Eosinophilic Gastroenteritis Associated with Persistent Blood Eosinophilia and Multiple Food Allergies - Polliana Mihaela Leru; Vlad Florin Anton; Ioana Adriana Muntean; Carmen Daniela Neagoe; Dumitru Matei (Diagnostics, 2022)
Eosinophilic gastroenteritis (EGE) is a subgroup of the eosinophilic gastro-intestinal disorders (EGIDs), characterized by eosinophilic infiltration and chronic inflammation of the gastrointestinal tract. These are rare diseases with still incompletely elucidated causes and mechanisms, with frequently delayed diagnosis and variable outcome. Despite increased interest in eosinophilic diseases in recent years, fewer data have been published on EGE and no standardized diagnostic and therapeutic approach exists. This paper reports the case of a young male patient diagnosed with EGE in 2017 based on clinical and histopathological criteria and constantly monitored during five years. Besides gastrointestinal eosinophilic infiltration, biopsies also revealed eosinophilic infiltration of the oesophagus, despite no declared characteristic oesophageal symptoms. We found increased specific IgE to multiple foods and progressive blood hypereosinophilia which preceded EGE diagnosis by three years. The EGE management included selective dietary restrictions and pharmacologic therapy based on daily budesonide non-enteric coated tablets, proton pumps inhibitors, antihistamines, cromoglycate, correction of iron, calcium and vitamin D deficiencies. The clinical outcome was good, while blood eosinophilia and endoscopic appearance remained almost unchanged. After one year the patient complained of respiratory symptoms suggesting asthma, needing continuous combined inhaled therapy. The reported case is illustrative for complex presentation, diagnosis and outcome of a rare case of mucosal chronic EGE associated with oesophageal involvement, peripheral eosinophilia, multiple food allergies and asthma.